2022
DOI: 10.3390/machines10080698
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics Optimization Research and Dynamics Accuracy and Reliability Analysis of a Multi-Link Mechanism with Clearances

Abstract: With the development of high-speed and lightweight mechanisms, and the continuous improvement of manufacturing accuracy requirements in industrial production, clearance joints have increasingly become one of the key factors affecting dynamics performance. Poor clearance will seriously compromise stability, accuracy, and dynamics performance. Based on a genetic algorithm, an efficient modeling methodology for the dynamics optimization of a planar complex multi-link mechanism containing multiple clearance joints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Eng. 2023, 11, x FOR PEER REVIEW where h(t − τ) is the complex frequency response function [37]; τ is the re dτ is per unit time; ωn is the natural angular frequency (undamped system ural angular frequency (damped vibration); and ζ is the damp ratio.…”
Section: Foundation Of the Dynamic Equationmentioning
confidence: 99%
“…Eng. 2023, 11, x FOR PEER REVIEW where h(t − τ) is the complex frequency response function [37]; τ is the re dτ is per unit time; ωn is the natural angular frequency (undamped system ural angular frequency (damped vibration); and ζ is the damp ratio.…”
Section: Foundation Of the Dynamic Equationmentioning
confidence: 99%
“…Song et al [34] found that when the link's flexibility was considered, the movement accuracy of a flexible parallel robot was reduced and the motion stability of the mechanism with flexible links was better than that only considering clearance joints. Jiang et al [35] proposed a modeling method for a multi-link mechanism considering the coupling effects of the clearance and flexibility, pointing out that the flexibility can effectively reduce the peaks of dynamic responses. Shen et al [36] established a dynamic model of a solar array system with flexible panels and clearance joints.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, mechanism chaos has been investigated by many researchers analytically and experimentally, and the majority of these works have concentrated on dynamic response analysis [13,14]. The main purpose of studying the dynamic response of mechanism with clearance joints is to improve the mechanism stability, accuracy, and dynamics performance, as clearance joints cannot be avoided due to various factors, but high-speed, lightweight, and high-precision mechanisms are required in industrial production [15,16]. Chen et al [17] presented a general dynamic model to study the slider-crank mechanism with multiple clearance joints, the stability and chaos analysis results were used to quantify the influence of clearance sizes and driving speeds.…”
Section: Introductionmentioning
confidence: 99%